The adaptation of medical vocabulary in child-patient narration (based on N. N. Nazarkin’s short-story collection “The Emerald Fish”) - Xulong Fang (Philology. Theory & Practice, 2026)
The study aims to identify the specific features of the adaptation of medical vocabulary in the narrative of a child patient, based on N. N. Nazarkin’s short-story collection “The Emerald Fish”. The scientific novelty lies in the fact that, for the first time, three interrelated aspects of the adaptation of medical vocabulary in the narrative of a child patient are distinguished on the basis of the stories in “The Emerald Fish”: structural and nominative features, contextually conditioned reference, and contextual explication. It has been established that differences between the levels of contextual explication correspond to the boundaries of the child narrator’s knowledge. The findings demonstrate that, at the level of structural and nominative features, adaptation manifests itself in the inclusion of conventional linguistic means of the hospital environment in the speech of child characters and in the situational transformation of individual units according to existing linguistic models. When a lexical unit is used in the literary work, its meaning limits the range of potential referents, while the immediate context and the characters’ shared background knowledge of hospital life make it possible to identify the specific referent. The context either supplies unexpressed information while preserving direct reference or induces a metonymic shift to a contiguous referent. Four levels of contextual explication of medical lexical items and information about the diagnostic and therapeutic procedures associated with them are identified: direct partial explanation; indirect explication through descriptions of diagnostic and therapeutic actions, observations of ongoing events, and bodily sensations; pragmatic inference; and the absence of additional explanation. When no additional explanation is provided, general-use medical lexical items function as part of the characters’ shared linguistic experience, while the conceptual content of certain specialized terms remains unexplicated for the reader. The system of identified levels reflects the combination of the child narrator’s experience-based knowledge of hospital life with a fragmentary and uneven acquisition of medical concepts.